Luxury fashion brands engagement and Social media – The case of Generation Y in Thailand - Pasuhirunnikorn, Nantanut (2017)
The growth of Generation Y consumers in the luxury fashion market has been phenomenal in recent decades, especially among emerging Asian countries. This research thus aims to understand the behaviour of this relatively new segment of consumers, a group that is now the biggest spender of $2.45 billion, especially in terms of their engagement with brands’ online channels i.e. social media. The literature review examined both theoretical underpinning and research study context. This present study employed social identity and social comparison theory as a conceptual lens to investigate Generation Y consumer behaviour on social media; by examining the Instagram platform. Quantitative primary data was gathered from 103 respondents via online self-completion surveys. The findings reveal that social-adjustive function, value-expressive function, social value and individual value are positively related to consumer brand engagement on social media. However, the amount of time spent on these digital channels cannot be used to predict the level of consumer brand engagement among Thai Generation Y users. The dissertation concludes with a discussion of findings, limitations of present investigation and suggestions for further research.